2016
DOI: 10.1111/aos.13025
|View full text |Cite
|
Sign up to set email alerts
|

The vasodilating effects of insulin and lactate are increased in precapillary arterioles in the porcine retina ex vivo

Abstract: ABSTRACT.Purpose: Disturbances in the diameter regulation of the larger retinal vessels are involved in the pathophysiology of a number of vision threatening retinal diseases, but the role of the smaller vessels has received less attention. Therefore, an experimental model was developed for studying diameter changes in retinal vessels at all branching levels secondary to pharmacological interventions ex vivo. Methods: Porcine hemiretinas were mounted in a tissue chamber that allowed the control of temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…5). Also similar to hypoxia and consistent with lactate's role as a vasodilator in the normal retinas (15,(19)(20)(21), arterioles within both control and >P40 ROP retinas-whose vessels were not suprahyperpolarized (Fig. 1C)-dilated in response to lactate (Fig.…”
Section: Electrogenic Basis For Neovesselsupporting
confidence: 67%
See 1 more Smart Citation
“…5). Also similar to hypoxia and consistent with lactate's role as a vasodilator in the normal retinas (15,(19)(20)(21), arterioles within both control and >P40 ROP retinas-whose vessels were not suprahyperpolarized (Fig. 1C)-dilated in response to lactate (Fig.…”
Section: Electrogenic Basis For Neovesselsupporting
confidence: 67%
“…Based on our earlier study of retinovessels (20), we considered a role for a cascade of events involving lactate, MCT, and NCX. Previously, we found that under certain conditions, the activation of this cascade can cause retinovessels to contract (20), although this vasoconstricting influence is usually vitiated by the potent vasorelaxing impact of lactate on precapillary arterioles (21), as well as on larger retinal arterioles, in which the activation of a voltage-changing K ATP current plays a key role (15). However, we posited that the relative impact of the lactate/MCT/NCX pathway would be boosted when suprahyperpolarization to a voltage near E K , as observed in <P30 ROP retinas (Fig.…”
Section: Electrogenic Basis For Neovesselmentioning
confidence: 99%
“…The experimental setup has been described in detail previously 11 and is shown in Figure 1. In short, a tissue chamber has been designed to hold a porcine hemiretina while controlling pH, temperature, and oxygen saturation.…”
Section: Mountingmentioning
confidence: 99%
“… 7 In porcine retinal arterioles, extravascular application of ATP agonists induces vasodilatation 8 , 9 and the ATP degradation product adenosine has dual effects on the tone of retinal arterioles with contraction and relaxation mediated by different receptors. 10 Recently, attention has been directed at different effects of intra- and extravascular application of vasoactive compounds 11 and the role of pre-capillary arterioles and capillaries for regulating retinal blood flow. 12 14 However, the effects of different routes of application of ATP and the role of the compound for the diameter regulation of smaller retinal vessels have not been studied in detail.…”
mentioning
confidence: 99%
“…Therefore, wherever possible, we usually try to validate key findings from our isolated arteriole preparations using ex vivo retinal whole-mounts and in vivo measurements of vessel diameter and blood flow 16 37 . Of note, new methods have recently emerged for studying small arterioles and capillaries in whole perfused porcine retinas ex vivo 38 39 . Such preparations are likely to greatly improve our understanding of how the retinal neuropile regulates retinal arteriolar and capillary tone and how changes in retinal haemodynamics modulate neuronal activity in the retina.…”
Section: Discussionmentioning
confidence: 99%